If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 1 + 6p = 4p + -14 Reorder the terms: 1 + p + 6p = 4p + -14 Combine like terms: p + 6p = 7p 1 + 7p = 4p + -14 Reorder the terms: 1 + 7p = -14 + 4p Solving 1 + 7p = -14 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 1 + 7p + -4p = -14 + 4p + -4p Combine like terms: 7p + -4p = 3p 1 + 3p = -14 + 4p + -4p Combine like terms: 4p + -4p = 0 1 + 3p = -14 + 0 1 + 3p = -14 Add '-1' to each side of the equation. 1 + -1 + 3p = -14 + -1 Combine like terms: 1 + -1 = 0 0 + 3p = -14 + -1 3p = -14 + -1 Combine like terms: -14 + -1 = -15 3p = -15 Divide each side by '3'. p = -5 Simplifying p = -5
| 23x+14y=283 | | 20-3m-1=-4 | | 3x+4(2x+2)=3 | | 4+5x=6+3x | | 4y+8=-26 | | 33+7x+10=13+2x | | 3.5(x+4)+4.5=2(-6.5) | | .66(1+n)=-.50n | | |-3a|=15 | | x^2+10+24= | | y=2/3(-1)-7 | | 9.06=51 | | -62u=60 | | 2y+6=-8 | | (x+4)(x-2)=7 | | y=2/3(1)-7 | | y=2/3(0)-7 | | 6b-38=-6b+14 | | 3(2x+1)=4x-13 | | 54=(4r-5) | | 8(f+8)=1 | | 2a-5(a-4)=-4 | | X+3x-12=180 | | 7=2t-5 | | X(3x-12)=180 | | 4x+(5+2x)=2 | | 5x+18-4=-36 | | x^2+6-30=0 | | 2r-45-19r=-53+r | | w-6=-48 | | y=4+(-2) | | -10-6x+4x=3-4x-1 |